Researching internet governance : methods, frameworks, futures - DeNardis, Laura; Cogburn, Derrick L.; Levinson, Nanette S.; Musiani, Francesca (Cambridge, Massachusetts : The MIT Press, 2020)
"Research concepts, methods, and frameworks for the study of internet governance, by leading scholars from law, computer science, communication, science and technology studies, and political science"--
Keywords: Governança da Internet; Internet -- Pesquisa qualitativa